2021
DOI: 10.2196/18799
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Online Health-Related Information Seeking in France From 2010 to 2017: Results From Nationally Representative Surveys

Abstract: Background Given the rapid ongoing progression of the internet and increase in health information available from disparate online sources, it is important to understand how these changes impact online health information-seeking behavior of the population and the way of managing one’s health. Objective This paper aims at describing the evolution of internet use as a source of health information between 2010 and 2017, as well as the characteristics of onl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Although the mobile interface may be more difficult for tasks such as OHIS [ 8 ], having at least one point of access is critical for web-based health behaviors [ 9 , 24 ]. Although some OHIS research suggests that access has been democratized [ 19 ], the above results highlight the overlap in health and technology disparities for racial and ethnic minority groups [ 4 - 6 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the mobile interface may be more difficult for tasks such as OHIS [ 8 ], having at least one point of access is critical for web-based health behaviors [ 9 , 24 ]. Although some OHIS research suggests that access has been democratized [ 19 ], the above results highlight the overlap in health and technology disparities for racial and ethnic minority groups [ 4 - 6 ].…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have identified additional second-level factors that may also impede technological adoption (eg, skills) [ 15 , 18 ]. Although the focus of OHIS has shifted away from access as some suggest that it has become democratized [ 19 ], we argue that it has not been democratized across devices and contexts of use as the lack of physical access remains an obstacle for marginalized groups [ 3 , 20 ]. Moreover, access is heterogeneous, as people can access the internet on multiple devices and at various places [ 7 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients' confidence in this therapeutic modality depends on many factors, including what they have read about treatment ( 9 11 ). Nowadays most sectors of the general population turn to the internet to search for medical information ( 12 , 13 ). According to a Pew Research Center survey, roughly seven-in-ten Americans use social media, a level that has remained relatively stable over the past several years ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…63 When a patient requests a medication, informed by DTCA, and the prescriber reviews and consents, should we always view this as a negative outcome? The counterfactual scenario of no DTCA may result in a patient with less awareness of their symptoms or treatment options, 13,21,60,64 obtaining information from sources not produced by the manufacturer (potentially reputable or nonreputable), 65,66 and potentially less activation in seeking a treatment. 13 In the wake of effective misinformation campaigns throughout the COVID-19 pandemic, 67 we are reminded health information availability and reliability are critical to advancing public health.…”
Section: Discussionmentioning
confidence: 99%